Sulphide removal using phytoremediation process - Koh, Rui Shuan (2016)
Rapid development in social and economic area has created a serious environment contamination of soil and groundwater. The discharge of toxic material and contaminant has increased significantly during the last few years. Hence, a cost-effective and environment friendly alternative method should be featured and phytoremediation process is fulfilling those characteristics. According to the environment quality regulation 2009, the standard and acceptable sulphide concentration in the spent sulphide caustic (SSC) for discharge from industrial need to be lower than 0.5 mg/L to meet the standards A and B. In this study, two separate experiments were conducted to identity the sulphide removal during the phytoremediation. The first experiment was the phytotoxicity test, conducted to investigate the range of the sulphide uptake by the Scirpus grossus plants. The second experiment was conducted via semi-batch phytoremediation process approach consists of adding a similar total amount of sulphide content to the Scirpus grossus plants over a seven-day period of time to investigate the removal of sulphide from SSC by Scirpus grossus during phytoremediation process. Throughout the experiment, the plants growth was observed physically to investigate the ability of the plant to survive and resist the sulphide contaminant. The sulphide concentration for each sample was analysed and the percentage of the withered plants was calculated. From the phytotoxicity test, the finding revealed the mass concentration above 50 g/L Na2S which consist of 5 mg/L is not suitable for the phytoremediation process and the mass of sodium sulphide for the further experiment should be less than 50 g/L Na2S for the phytoremediation process using Scirpus grossus plants. From the semi-batch experiment, the results shown the percentage of the withered leaves increase throughout the semi-batch process and the sample Scirpus grossus plants with 1.2 g/L of Na2S shows the highest percentage of withered leaves due to the highest sulphide content in the synthetic SSC. The Scirpus grossus plants with 0.4 g/L and 0.8 g/L of Na2S show the highest percentage of removal which reaching more than 70 % throughout the experiment. In addition, the pH and Chemical Oxygen Demand (COD) were measured throughout the experiment. The pH is in the range of 7.8 to 11.9 while the COD in the range of 54.7 mg/L to 912 mg/L. In short, the finding revealed that phytoremediation process is possible to be used for sulphide removal using Scirpus grossus plants.